2016
DOI: 10.1097/mpa.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol in Pancreatic β-Cell Death and Dysfunction

Abstract: The mechanisms or causes of pancreatic β-cell death as well as impaired insulin secretion, which are the principal events of diabetic etiopathology, are largely unknown. Diabetic complications are known to be associated with abnormal plasma lipid profile, mainly elevated level of cholesterol and free fatty acids. However, in recent years, elevated plasma cholesterol has been implicated as a primary modulator of pancreatic β-cell functions as well as death. High-cholesterol diet in animal models or excess chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 119 publications
0
10
0
2
Order By: Relevance
“…Excessive intracellular cholesterol renders in pancreatic beta cells dysfunctional . In this study, mice under HCD remained euglycemic but became hyperinsulinemic, an indication that they were insulin resistant, as translated by their decreased GIR values.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Excessive intracellular cholesterol renders in pancreatic beta cells dysfunctional . In this study, mice under HCD remained euglycemic but became hyperinsulinemic, an indication that they were insulin resistant, as translated by their decreased GIR values.…”
Section: Discussionmentioning
confidence: 55%
“…We previously reported that PCSK9 knockout (PCSK9KO) mice had more LDLR and cholesterol in their islets . Intracellular accumulation of cholesterol is known to deleteriously affect the endocrine function of β cells . It is presumably a cause of the insulin‐insufficiency and the prediabetes exhibited by PCSK9KO mice .…”
Section: Introductionmentioning
confidence: 99%
“…The lower risk of T2DM appeared in a large LDL cholesterol range, and the LDL cholesterol concentration did not significantly affect T2DM risk. Although there is in-vivo and ex-vivo evidence showing that LDL concentration modulates insulin secretion and pancreatic β-cell survival 13 , large prospective studies showed no significant effect of LDL cholesterol on T2DM risk, in contrast to the association with high triglycerides or low HDL cholesterol that has been repeatedly demonstrated 14, 15 . In human β cell islets, LDL overload lowered insulin secretion 16 and diet-induced hypercholesterolemia also reduced insulin secretion in mice 17 ; however, this diabetogenic effect of hypercholesterolemic diets has also been associated with saturated fatty acid accumulation rather than with cholesterol 16, 18 .…”
Section: Discussionmentioning
confidence: 98%
“…6,16 Moreover, excessive accumulation of cholesterol appears to play an important role in beta-cell function. 17,18 The increased uptake of low-density lipoprotein cholesterol by islet beta-cells and subsequent oxidative reactions were shown to be detrimental for these cells. 17,19 Unsaturated fatty acids, on the other hand, were associated with a variety of beta-cell protective effects, including prevention of beta-cell apoptosis and enhanced insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%